Piperazine ferulate exerts antihypertensive effect and improves endothelial function in vitro and in vivo via the activation of endothelial nitric oxide synthase - Jianzhi, Shao; Qizeng, Wang; Bin, Lin; Wenhui, Lin; Yunpeng, Chen; Chenrong, Fan; Lin, Zheng; Huiting, Chen (Cellular and Molecular Biology, 2019)
To investigate the effect of piperazine ferulate (PF) on hypertension and endothelial function, and to assess the possible underlying mechanism. Human umbilical vein endothelial cells (HUVEC), adult male Wistar Kyoto (WKY) rats aged 12 to 14 weeks, and spontaneously hypertensive (SH) and Sprague Dawley (SD) rats were used for this study. Cell viability, activities of angiotensin-converting enzyme (ACE) and heme oxygenase-1 (HO-1), in vivo NO synthesis, arterial systolic blood pressure, vascular function, expressions of endothelial NO synthase (eNOS) and phosphorylated-eNOS (p-eNOS) were determined or assessed as appropriate. The results of MTT assay showed the number of viable cells were significantly increased with increase in PF concentration (p < 0.05). The level of expression of ACE was significantly reduced with increase in PF concentration (p < 0.05), while the level of HO-1 expression significantly increased (p < 0.05). Results of DAF-FM fluorescent staining showed that the amounts of NO synthesized in vivo was significantly higher in aortic rings of SH and SD rats treated with PF than in the corresponding control groups (p < 0.05). Treatment with PF in vivo significantly improved impaired acetylcholine-induced aortic relaxation in SH rats. Total eNOS expression was significantly increased after treatment with PF (p < 0.05). The expressions of total eNOS and p-eNOS in both groups were not affected by PF when compared to the control group. These results indicate that PF exerts antihypertensive effect and improves endothelial function in vitro and in vivo via the activation of eNOS.